Clinico-microbiological profile of Burkholderia cepacia keratitis: a case series - Ming-Chih Ho; Eugene Yu-Chuan Kang; Lung-Kun Yeh; David H. K. Ma; Hsin-Chiung Lin; Hsin-Yuan Tan; Hung-Chi Chen; Ching-Hsi Hsiao (BMC, 2021)
Abstract Background Burkholderia cepacia, an opportunistic pathogen mainly affecting patients with cystic fibrosis or immunocompromised, has rarely been documented as a cause of corneal infection. The clinical and microbiological profiles of B. cepacia keratitis are reported herein. Methods We retrospectively reviewed the medical record of 17 patients with culture-proven B. cepacia keratitis, treated between 2000 and 2019 at Chang Gung Memorial Hospital, Taiwan. Our data included predisposing factors, clinical presentations, treatments, and visual outcomes of B. cepacia keratitis as well as the drug susceptibility of the causative agent. Results The most common predisposing factor for B. cepacia keratitis was preexisting ocular disease (seven, 41.2%), particularly herpetic keratitis (five). Polymicrobial infection was detected in seven (41.2%) eyes. All B. cepacia isolates were susceptible to ceftazidime. Main medical treatments included levofloxacin or ceftazidime. Surgical treatment was required in five (29.4%) patients. Only four (23.5%) patients exhibited final visual acuity better than 20/200. Conclusions B. cepacia keratitis primarily affects patients with preexisting ocular disease, particularly herpetic keratitis, and responds well to ceftazidime or fluoroquinolones. However, the visual outcomes are generally poor.